2010
DOI: 10.3892/or_00000885
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of stem-like populations with elevated ALDH1 in sarcomas for chemotherapeutic drug resistance

Abstract: Abstract. Elevated aldehyde dehydrogenase 1 (ALDH1) has been proposed as one of the possible candidates for a stem cell maker that can be used for the isolation of cancer stem cells from cancers such as leukemia and breast cancer. In the current study, we found that subpopulations with elevated ALDH1 were present in the human sarcoma cell lines, MG63 (osteosarcoma) and HT1080 (fibrosarcoma), using Aldefluor assay. Both ALDH1 positive and negative cell populations were isolated from the MG63 cell line, by cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 31 publications
5
95
0
Order By: Relevance
“…The sphere-forming capacity in established osteosarcoma cell lines has been previously demonstrated (4,8,9,11,12). Interestingly, Honoki et al showed that the frequency of sphere formation was 0.25% in ALDH1-positive MG-63 cells (9). Moreover, primary cultures of osteosarcoma tended to have enhanced sphere-forming capacities (5,8,16).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The sphere-forming capacity in established osteosarcoma cell lines has been previously demonstrated (4,8,9,11,12). Interestingly, Honoki et al showed that the frequency of sphere formation was 0.25% in ALDH1-positive MG-63 cells (9). Moreover, primary cultures of osteosarcoma tended to have enhanced sphere-forming capacities (5,8,16).…”
Section: Discussionmentioning
confidence: 95%
“…The proteasome activity of ZsGreen + cells are lower than ZsGreen -cells in MG-63, whereas no difference was found in U2-OS; this is likely because this proteasome activity assay can detect partial proteasome activity. The sphere-forming capacity in established osteosarcoma cell lines has been previously demonstrated (4,8,9,11,12). Interestingly, Honoki et al showed that the frequency of sphere formation was 0.25% in ALDH1-positive MG-63 cells (9).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A subpopulation of ALDH1 high MG63 cells was detected by Honoki et al (25) who further reported ALDH1 high cells to have increased expression of stem-like genes (Nanog, Oct3/4, Stat3, Sox2), higher resistance to doxorubicin and cisplatin and increased self-renewal ability as shown by sphere formation. Importantly, ALDH high cells were also detected in human osteosarcoma samples and increased ALDH activity was further correlated to metastatic potential (26).…”
Section: Aldehyde Dehydrogenase (Aldh)mentioning
confidence: 98%
“…Therefore, the generation of MIC properties may be phenotypically linked to enhanced drug resistance capacities. MICs enriched with CSC-like features may benefit from resistant mechanisms of CSCs, such as a stronger DNA damage response (Wang 2015), elevated expression of efflux drug pumps (Schinkel et al 1994;Zhou et al 2001;Dean et al 2005), and ALDH detoxifying enzymes (Honoki et al 2010;Rausch et al 2010). Therefore, inhibitors of pathways involved in CSC regulation, such as antibodies against NOTCH, FZD, IL6R, and other relevant signaling pathway receptors, may also have a therapeutic impact on MICs (Brooks et al 2015).…”
Section: Drug Resistance Of Micsmentioning
confidence: 99%